Novel Osmium‐based Coordination Complexes as Photosensitizers for Panchromatic Photodynamic Therapy. (13th June 2017) - Lazic, Savo; Kaspler, Pavel; Shi, Ge; Monro, Susan; Sainuddin, Tariq; Forward, Sarah; Kasimova, Kamola; Hennigar, Robie; Mandel, Arkady; McFarland, Sherri; Lilge, Lothar
Abstract: Cancer remains a major global malaise requiring the advent of new, efficient and low‐cost treatments. Photodynamic therapy, which combines a photosensitizer and photons to produce cytotoxic reactive oxygen species, has been established as an effective cancer treatment but has yet to become mainstream. One of the main limitations has been the paucity of photosensitizers that are effective over a wide range of wavelengths, can exert their cytotoxic effects in hypoxia, are easily synthesized and produce few if any side effects. To address these shortfalls, three new osmium‐based photosensitizers (TLD1822, TLD1824 and TLD1829) were synthesized and their photophysical and photobiological attributes determined. These photosensitizers are panchromatic ( i.e . black absorbers), activatable from 200 to 900 nm and have strong resistance to photobleaching. In vitro studies show photodynamic therapy efficacy with both red and near‐infrared light in normoxic and hypoxic conditions, which translated to good in vivo efficacy of TLD1829 in a subcutaneous murine colon cancer model. Abstract : Coordination complexes are gain rapidly attention as a central building block for photosensitizer in photodynamic Therapy. Initial coordination complexes Ruthenium‐based photosensitizers are often limited in their ability to absorb light in the red spectral range. Using osmium as central photosensitizer alleviates this spectral limitation. Here, three different Os(II) constructs with π‐extended 2, 2′‐biquinoline (biq) ligands, are investigated photochemical and photobiological, in vitro as well as in vivo . These studies identified [Os(biq)2 (Imidazo[4, 5‐f][1, 10]phenathroline)](PF6)2 as the preferred photosensitizer among the three tested, for further extended in vivo studies.